Internalization of Falsafah Peri Mestike Gayo as an Effort To Developing Students Characters Based on Local Authority In SMA 1 Takengon Aceh Central District - Indra, Indra; Rasyidin, Al; Sukiman, Sukiman (Universitas Malikussaleh, 2019)
At present, there are two trending topic studies in the world of education that are hotly discussed, namely character education and local wisdom (indigenization).